The earnings returns to graduating with honors: Evidence from law graduates - Ronny Freier; Mathias Schumann; Thomas Siedler (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This paper studies the causal effects of graduating from university with an honors degree on subsequent earnings. While a rich body of literature has focused on estimating returns to human capital, few studies have analyzed returns at the very top of the education distribution. We highlight the importance of honors degrees for future labor market success in the context of German law graduates. Using a difference-in-differences research design combined with entropy balancing, we find that students of law who passed the state bar exam with an honors degree receive a significant earnings premium of about 14 percent. The results are robust to various sensitivity analyses.
Keywords: J01; J31; J44; 330; returns to education; difference-in-differences; entropy balancing; law graduates; earnings